Infection Control During Gastrointestinal Endoscopy - Douglas B Nelson; Paul C Adams (Canadian Journal of Gastroenterology)
Dr Douglas Nelson is a staff physician in the department of gastroenterology at the Minneapolis VA Medical Center (Minnesota, USA) and a Professor of Medicine at the University of Minnesota (USA). He has written numerous articles on the subject of infection control during gastrointestinal endoscopy, and was the lead author of the "Multi-society guideline for reprocessing flexible gastrointestinal endoscopes" (1).